Do electricity prices matter? Plant-level evidence from German manufacturing - Andreas Gerster (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
In many countries, the transition process towards a low-carbon economy has been associated with increasing electricity prices. Microeconometric evaluations of the causal impact of electricity price changes on plant-level outcomes are rare, though. By exploiting local randomization induced by thresholds in exemption rules, we estimate the local average treatment effects of electricity levy exemptions using a fuzzy regression discontinuity (RD) design. The results indicate that exempted German manufacturing plants increase electricity use substantially and substitute it for fossil fuels, while we do not find evidence for short-run effects on gross output, exports and employment. – – In vielen Ländern führt eine fortschreitende Dekarbonisierung der Wirtschaft zu höheren Strompreisen. Mikroökonometrische Evaluierungen der kausalen Effekte sich verändernder Strompreise auf Betriebe des Verarbeitenden Gewerbes sind allerdings rar. Dieser Artikel nutzt Schwellenwerte bei der Festlegung von Berechtigungen zur Befreiung von der EEG-Umlage um die durchschnittlichen Treatmenteffekte dieser Befreiung über eine Regressions-Diskontinuitäts-Analyse zu schätzen. Die Ergebnisse zeigen, dass befreite Betriebe ihren Stromverbrauch beträchtlich steigern und den Anteil fossiler Energien am Energieverbrauch senken. Demgegenüber können keine Effekte auf Umsatz, Exporte oder die Beschäftigung nachgewiesen werden.
Keywords: D22; H23; L60; Q41; Q48; 330; environmental taxation; electricity prices; manufacturing; regression discontinuity design